Village of Oregon citizen survey report, 2010 - Janke, James; Trechter, David; Hadley, Shelly (My University, 2010)
The purpose of this study was to gather public input for a strategic plan for the Village of Oregon government.
27 p.
Keywords: Survey; UWRF Survey Research Center; UWRF Survey Research Center Report; Public opinion survey; Community planning; Comprehensive plan report; Comprehensive plan; Dane County, Wisconsin; Dane County (Wis.); Village of Oregon; Oregon (Wis. : Village); Oregon (Wis. : Village)--Surveys; Public opinion--WIsconsin--Oregon (Village); Land use--Wisconsin--Oregon (Village); City planning--Wisconsin--Oregon (Village)